Komunikasi dalam Era Teknologi Komunikasi Informasi - Erni Herawati (Bina Nusantara University, 2011)
Globalization and the advancement of information and communication technology has helped people to communicate in ways we never imagined before. The computer technology advancement has been attached to communication tools, like radio, television, telephone, cellular phone, smart phone, or even tablets PC; has made people around the world, including Indonesia, is going to globalized communication changing. Human culture is always developed according to the existing technology advancement. Thus information technology is growing with many variants that made people keep looking for the latest invention in communicating. Communication that facilitated by new mediums has made communication theorists look back to the previous communication theories.